PROFIL PELAJAR PANCASILA DALAM PEMBELAJARAN ERA SOCIETY 5.0 - Kalvin Karuna; Henderika Serpara; June Noya van Delsen (Universitas Pattimura, 2023)
This community service activity aims to (a) provide teachers with an understanding of the nature of the Pancasila Students Profile, including its definitions, dimensions, elements, and sub elements. (b) provide teachers with an understanding of Era Society 5.0. (c) describe the integration of dimensions and elements of the Pancasila Student Profile and the skills of Era Society 5.0. The method of delivering the material is a presentation interspersed with questions and answers. At the end of the activity, a reflection was conducted to determine the participants' understanding of the material and the relevance of the material to the learning needs at school. The results of the reflection showed that, a. organizationally, the activity went well because of the good coordination between the FKIP UNPATTI PPG team and the partners, b. the Pancasila Student profile material integrated the latest learning elements in the 21st century, and c. the material presented was received positively by all participants. The response is based on the results of the reflection that the method of presenting the material allows participants to easily understand it because it is presented in simple language and is interactive with concrete examples. The material that has been learned can be applied to learning in their respective education units and even shared in the form of good practices with other communities because the material is relevant to the learning needs.